Pyrido[2',1':2,3]imidazo[4,5-c]isoquinolin-5-amines as Potential Cytotoxic Agents against Human Neuroblastoma - Zahira Tber; Mohammed Loubidi; Jabrane Jouha; Ismail Hdoufane; Mümin Alper Erdogan; Luciano Saso; Güliz Armagan; Sabine Berteina-Raboin (MDPI AG, 2021)
We report herein the evaluation of various pyrido[2',1':2,3]imidazo[4,5-c]isoquinolin-5-amines as potential cytotoxic agents. These molecules were obtained by developing the multicomponent Groebke-Blackburn-Bienaymé reaction to yield various pyrido[2',1':2,3]imidazo[4,5-c]quinolines which are isosteres of ellipticine whose biological activities are well established. To evaluate the anticancer potential of these pyrido[2',1':2,3]imidazo[4,5-c]isoquinolin-5-amine derivatives in the human neuroblastoma cell line, the cytotoxicity was examined using the WST-1 assay after 72 h drug exposure. A clonogenic assay was used to assess the ability of treated cells to proliferate and form colonies. Protein expressions (Bax, bcl-2, cleaved caspase-3, cleaved PARP-1) were analyzed using Western blotting. The colony number decrease in cells was 50.54%, 37.88% and 27.12% following exposure to compounds 2d, 2g and 4b respectively at 10 μM. We also show that treating the neuroblastoma cell line with these compounds resulted in a significant alteration in caspase-3 and PARP-1 cleavage.